The Flow of Disbursement Regional Government Budget - Nurul Nihlah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Politeknik Piksi Input Serang, 2022)
Purpose - This is where you explain ‘why’ you undertook this study. If you are presenting new or novel research, explain the problem that you have solved. If you are building upon previous research, briefly explain why you felt it was important to do so. This is your opportunity to let readers know why you chose to study this topic or problem and its relevance. Let them know what your key argument or main finding is Design/methodology/approach - This is ‘how’ you did it. Let readers know exactly what you did to reach your results. For example, did you undertake interviews? Did you carry out an experiment in the lab? What tools, methods, protocols or datasets did you use? Finding - Here you can explain ‘what’ you found during your study, whether it answers the problem you set out to explore, and whether your hypothesis was confirmed. You need to be very clear and direct and give exact figures, rather than generalise. It’s important not to exaggerate or create an expectation that your paper won’t fulfill. Originality -